Manuals and protocols for conservation and sustainable use of agrobiodiversity - Vernooy, Ronnie (2023)
This document presents nine manuals and protocols for the conservation and sustainable use of agrobiodiversity. The manuals and protocols included target a variety of trainees and end-users, including extensionists, farmers, facilitators and researchers.